The classification and phylogeny of the Psocoptera - Smithers, Courtenay Neville (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 1970)
This work provides a phylogenetic classification of the insect order PSOCOPTERA. Some of the problems involved, mainly arising from lack of adequate published data, are pointed out and work carried out to overcome them is indicated in a short introductory chapter (Chapter I). This consisted of accummulating data on the genera from published texts and illustrations, adding data from the study of fresh material or material held in collections and compiling generic definitions in adequate detail where possible. Chapter II gives a general description of the Psocoptera together with brief background information on their biology. As considerable changes are proposed in the classification of the order (in Chapter VII) the classification in use at present is set out for comparison to generic level and a brief history of systematic work on the order is given {Chapter III). The data necessary for a discussion of the phylogeny is presented in the series of definitions of genera and suprageneric groups in Chapter IV. Data on fossil forms is given in Chapter V. The principles of phylogenetic study are briefly discussed in Chapter VI and the important question of the relatively primitive or advanced condition of characters in the order is discussed. The monophyly of the order and the relationships between genera are established using Hennig's system and the results are set out in discussion and dendrogram. On the basis of the relationships so established a classification of the order is proposed which is considered to be practical and to reflect evolutionary history of the group. (Chapter. VII.) Comments on the distribution of the Psocoptera are made in Chapter VIII and it is suggested that, despite inadequacy of data, a consideration of the distributions supports the proposed classification in general terms. A general discussion follows and references and figures are included. An appendix provides a practical up-to-date key to the genera of the order.
Keywords: Psocoptera; Insects -- Classification